Plasmonic Properties of Nano- and Microscale Dielectric Substrates-Supported Nanoshell Dimers: Effects of Type and Propagation Direction of Excitation Light - Gour Mohan Das; Venkata Ramanaiah Dantham; Akash Arya (IEEE Photonics Journal, 2019)
Herein, we report a finite element method simulated near-field spectra of single nanoshell dimers placed over nano- and microscale dielectric substrates. The simulations have been carried out on an individual basis for the top and bottom illuminated nanodimers with a plane wave and a focused Gaussian beam. Only one peak has been observed in the near-field spectra of free-standing and nano-scale substrate-supported nanodimers, due to the constructive coupling of fundamental modes of nanoshells at the nanogap. The wavelength location of the peak has been slightly red shifted in the presence of the nano-scale dielectric substrate. But, the obtained spectra have been found nearly independent with the type and direction of propagation of excitation light $({\boldsymbol k}_{exc})$ . However, multiple peaks have been noticed in the near-field spectra in the presence of microscale substrates due to the constructive coupling of lower as well as higher order modes (multipolar modes) of nanoshells at the nanogap. In contrast, the near-field spectra have been found sensitive to all dimensions of the substrate, the type of excitation light, and the direction of $({\boldsymbol k}_{exc})$ . Moreover, the far-field scattering spectra of a microscale substrate supported nanodimers have also been found sensitive to the direction of $({\boldsymbol k}_{exc})$ .